2011
DOI: 10.3791/2389
|View full text |Cite
|
Sign up to set email alerts
|

The Culture of Primary Motor and Sensory Neurons in Defined Media on Electrospun Poly-L-lactide Nanofiber Scaffolds

Abstract: Electrospinning is a technique for producing micro-to nano-scale fibers. Fibers can be electrospun with varying degrees of alignment, from highly aligned to completely random. In addition, fibers can be spun from a variety of materials, including biodegradable polymers such as poly-L-lactic acid (PLLA). These characteristics make electrospun fibers suitable for a variety of scaffolding applications in tissue engineering. Our focus is on the use of aligned electrospun fibers for nerve regeneration. We have prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…In correspondence with our results, others have shown that primary neurons polarize in parallel with fiber orientation [19]. In the CNS, neuronal networks are highly complex and ordered structures with neurons extending often long axons/dendrites in a directed fashion.…”
Section: Topography Influence Hnpc Nuclei Alignment and Migration Ratsupporting
confidence: 78%
“…In correspondence with our results, others have shown that primary neurons polarize in parallel with fiber orientation [19]. In the CNS, neuronal networks are highly complex and ordered structures with neurons extending often long axons/dendrites in a directed fashion.…”
Section: Topography Influence Hnpc Nuclei Alignment and Migration Ratsupporting
confidence: 78%
“…Briefly, rats were decapitated and DRG were collected by microdissection into sterile calcium-and magnesium-free modified Hank's balanced salt solution (HBSS) (Sigma Aldrich; Lonza, Belgium) (7,20,22). The dorsal root ganglia from each rat were digested with trypsin (0.25% trypsin-0.02% EDTA) (Gibco; OK, US) at 37°C for 10 min.…”
Section: +mentioning
confidence: 99%
“…Typically, in primary cultures of mammalian brain neurons, the cells are plated with a relatively high density, on coated coverslips without a glial feeder layer (e.g., [31][32][33][34][35][36][37][38][39] ). When the plating density of neurons is reduced using this method, the initial lack of glial sheet leads to poor neuronal growth and dendritic extension (panels B, C in Figures 8-10), as reported previously [40][41][42] , probably due to poor glial growth 43,44 .…”
Section: Neuronal Culturesmentioning
confidence: 99%